Internalization of Character Education during the Covid-19 Pandemic through Entrepreneurship Education: Systematic Literature Review (SLR) - Lia Anggraini Mulyono; Bhima Erlangga Sukma Prayoga; Aniek Indrawati; Ludi Vishnu Wardana; Angga Martha Mahendra (FKIP, Universitas Palangka Raya, 2023)
This study aims to look at the process of internalizing character education during the COVID-19 pandemic through entrepreneurship education as a general subject of higher education in Indonesia. The method used in this research is Systematic Literature Review (SLR) by collecting and analyzing journals related to keywords. During the COVID-19 pandemic, universities implemented distance learning so that learning could continue, this made the process of internalizing character education through entrepreneurship education continue, through three stages, carried out in stages and continuously, namely 1) The value transformation stage, with presentations, discussions , and questions and answers through the digital platform Zoom or Google Meet. 2) The value transaction stage, carried out by field observations and virtual interviews with entrepreneurs. 3) The internalization stage, carried out in virtual practice by participating in the entrepreneurship program organized by the Directorate General of Higher Education in Independent Learning-Independent Campus (MBKM). Students at the end have the values of character education and entrepreneurial character, namely having high responsibility, hardworking, creative, independent, democratic traits and attitudes, love for the motherland, national spirit, achievement, socializing, peace-loving, fond of reading, and cares about the social environment, and has the characteristics of courage, wisdom, confidence, and foresight in seeing opportunities. Students with it will behave well, have sympathy, empathy, and know what is good and what is bad.